2012
DOI: 10.1016/j.biortech.2012.02.083
|View full text |Cite
|
Sign up to set email alerts
|

High nutrient removal rate from swine wastes and protein biomass production by full-scale duckweed ponds

Abstract: Duckweed ponds have been successfully used in swine waste polishing, generating a biomass with high protein content. Therefore, the present study evaluated the efficiency of two full-scale duckweed ponds considering nutrient recovery from a piggery farm effluent (produced by 300 animals), as well as the biomass yield and crude protein (CP) content. A significant improvement in the effluent quality was observed, with the removal of 98.0% of the TKN (Total Kjeldahl Nitrogen) and 98.8% of the TP (Total Phosphorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 19 publications
9
106
0
6
Order By: Relevance
“…As a result of the higher NO 3 À AN concentrations (approximately 8 mg/L) in summer and autumn (from agricultural wastewater washed by rain), the influent TN concentrations, conversely, were significantly higher (P < 0.05) in summer and autumn than in winter and spring. Table 2 also shows that the effluent NO 3 À AN concentrations of DWS and WHS were significantly higher (P < 0.05) than the influent in winter and spring, which was most likely because of the nitrification by nitrifying bacteria (Mohedano et al, 2012). The higher mat density of water hyacinth might have resulted in significantly lower (P < 0.05) dissolved oxygen concentrations (DO) and pH in the WHS than in the DWS throughout the year (Table 2).…”
Section: Nutrient Recovery and Removal From Wastewatermentioning
confidence: 95%
“…As a result of the higher NO 3 À AN concentrations (approximately 8 mg/L) in summer and autumn (from agricultural wastewater washed by rain), the influent TN concentrations, conversely, were significantly higher (P < 0.05) in summer and autumn than in winter and spring. Table 2 also shows that the effluent NO 3 À AN concentrations of DWS and WHS were significantly higher (P < 0.05) than the influent in winter and spring, which was most likely because of the nitrification by nitrifying bacteria (Mohedano et al, 2012). The higher mat density of water hyacinth might have resulted in significantly lower (P < 0.05) dissolved oxygen concentrations (DO) and pH in the WHS than in the DWS throughout the year (Table 2).…”
Section: Nutrient Recovery and Removal From Wastewatermentioning
confidence: 95%
“…5,6 The free-floating aquatic plant, Lemna minor, is considered to be an ideal test system for water remediation research [7][8][9] because of its physiological properties (small size, big surface) and high multiplication rate. 10,11 Lemna minor is considered one of the fastest growing plants, with a productivity of 10-30 tons of dry mass/ha·year, confirmed by Bich, 12 having a good capacity to adapt to different conditions, like a wide range of pH (4.5-8.3), temperature (6-33 °C), and different kinds of wastewaters. 13,14 Recent studies have reported that Lemna minor has great potentials in the phytoremediation of inorganic pollutants.…”
Section: Introductionmentioning
confidence: 94%
“…Lemnoideae is used as feed organisms for animals [4,5], treatment agents for the treatment of domestic and industrial wastewater [6,7], raw materials for biofuel production [8]. Interest in waste water as treatment agents of polluted water in fish farms is justified by the intensity of removal of biogenic elements and the possibility of efficient utilization of the growth of plant biomass as food for fish [9].…”
Section: K O Z a Rmentioning
confidence: 99%
“…Thus, even when treatment heavily contaminated wastewater in ponds with Lemnoideae processes of extraction of ammonium nitrogen and phosphates proceed several times faster than by nitrification followed by denitrification [5].…”
Section: N K O R E N C H U Kmentioning
confidence: 99%